Mikhail Bulgakov’s Stalin. Mihail Bulgakov, “Batum”, A play in 4 acts, Translation, notes and introductory study by Nicolae Bosbiciu, Cluj-Napoca, Eikon Publishing House, 2015 - WOHL, Eugen (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
For all the readers fascinated by Mikhail Bulgakov’s novels, most notably his masterpiece The Master and Margarita, as well as for all those interested in Bulgakov’s theatre, the recent Romanian translation of Batum, published in 2015 by the Eikon Publishing House, will definitely represent a pleasant surprise. A long overdue project, the play was written in 1939 (commissioned by the Moscow Art Theatre to celebrate Stalin’s 60th anniversary, yet later banned and never staged), the publishing in Romanian translation of Bulgakov’s last play, an elaborate project undertaken by the professor and researcher Nicolae Bosbiciu, represents an important piece in the puzzle that was the Russian author’s complicated relationship with the dictator Joseph Stalin. The author’s “obsession” was ignited by Stalin’s phone call on April 18th, 1930 and his promise of a future meeting between the two, an event that, as the translator states in his extensive introductory study, determined the Russian author to become “haunted by horrific neurasthenia and by his fixation on the promised meeting between him and Stalin” (p. 113).